Protein phosphatase type 2C PP2CA together with ABI1 inhibits SnRK2.4 activity and regulates plant responses to salinity. (1st December 2016) - Krzywińska, Ewa; Kulik, Anna; Bucholc, Maria; Fernandez, Maria A.; Rodriguez, Pedro L.; Dobrowolska, Grażyna
ABSTRACT: Protein phosphatases 2C (PP2Cs) are important regulators of plant responses to abiotic stress. It is established that clade A PP2Cs inhibit ABA-activated SNF1-related protein kinases 2 (SnRK2s). Our recently published results show that ABI1, a member of clade A of PP2C is also a negative regulator of SnRK2.4, a kinase not activated in response to ABA. Here, we show that another member of this clade - PP2CA, interacts with and inhibits SnRK2.4. The salt-induced SnRK2.4/SnRK2.10 activity is higher in abi1–2 pp2ca-1 mutant than in wild type or single abi1 or pp2ca mutants, indicating that both phosphatases are inhibitors of SnRK2.4 and are at least partially redundant. Moreover, PP2CA together with ABI1 and SnRK2.4 regulates root growth in response to salinity.